Research on Aero Engine Empower Development Strategy - Xiang Qiao; Huang Jindong; Hu Xiaoyu; Yan Wuying; Hou Wei (中国工程科学, 2022)
Aero engine is crucial for aircraft and its development level reflects a country's comprehensive strength, industrial base, and scientific and technological level. Studying strategies for strengthening the aero engine development in China is significant for technological innovation and high-quality development of China's manufacturing industry. In this study, we explore the significance for strengthening the aero engine development from the aspects of promoting national competitiveness, green development, and innovation-driven development, and summarize the experience of developed countries in aero engine development. Subsequently, we summarize the development status of China's aero engine industry, analyze the challenges urgently faced by the industry, and propose the connotation, objectives, and specific development path of the strategy in terms of advanced products, major infrastructure, common key technologies, and basic research. Furthermore, we propose the following suggestions to promote the high-quality development of China's aero engine industry: improving the policy and regulation systems, deepening industry system reforms, optimizing the industry operation mechanism, and improving the talents training system.